2021
DOI: 10.3386/w28958
|View full text |Cite
|
Sign up to set email alerts
|

The Great Unequalizer: Initial Health Effects of COVID-19 in the United States

Abstract: Skinner provided helpful comments. We thank Erik Hurst, Heidi Williams, and Timothy Taylor for very useful comments and suggestions on a previous draft of the paper. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The impact of Covid‐19 on social movements highlights its intersections with racial justice and #Black Lives Matter organizing (Bolsover, 2020; Godley et al., 2020; Hammonds, 2021) and global environmental justice, feminist and human rights mobilizing (Corpuz, 2021; Grant & Smith, 2021; Reyes, 2020). As Covid‐19 has sharpened the lens on the contributing, pre‐existing population health harms of global capitalism (Aguirre, 2020; Alsan et al., 2021; Bambra et al., 2020) and environmental inequalities (OECD, 2020; Perkins et al., 2021; Von Storch et al., 2021), social movements research has identified a decentralized, global “wave” of movements for social and economic justice organizing to fight capitalism and state power at a “moment of political suspension and heightened social confrontation” (Gerbaudo, 2020, p. 61) 3 . Covid‐19 points to the critical intervention of the pandemic and the potential for future mobilizing around structural inequalities, and theorizing Covid‐19 as a health social movement offers a key lens through which to view the historical foundations of and futures for pandemic social change.…”
Section: Social Movement Organizing and Emotion In Covid‐19mentioning
confidence: 99%
“…The impact of Covid‐19 on social movements highlights its intersections with racial justice and #Black Lives Matter organizing (Bolsover, 2020; Godley et al., 2020; Hammonds, 2021) and global environmental justice, feminist and human rights mobilizing (Corpuz, 2021; Grant & Smith, 2021; Reyes, 2020). As Covid‐19 has sharpened the lens on the contributing, pre‐existing population health harms of global capitalism (Aguirre, 2020; Alsan et al., 2021; Bambra et al., 2020) and environmental inequalities (OECD, 2020; Perkins et al., 2021; Von Storch et al., 2021), social movements research has identified a decentralized, global “wave” of movements for social and economic justice organizing to fight capitalism and state power at a “moment of political suspension and heightened social confrontation” (Gerbaudo, 2020, p. 61) 3 . Covid‐19 points to the critical intervention of the pandemic and the potential for future mobilizing around structural inequalities, and theorizing Covid‐19 as a health social movement offers a key lens through which to view the historical foundations of and futures for pandemic social change.…”
Section: Social Movement Organizing and Emotion In Covid‐19mentioning
confidence: 99%
“…This constitutes a three-level random effects meta-analysis where we allow a distribution over campaign effects, a distribution within each campaign across questions, and then a final distribution over observed experiment effects conditional on the true treatment effect. We parametrize this similarly as three nested normals: for a campaign i and question q, the distribution of true campaign effects, β i , is N ( β, τ 2 1 ); the distribution over question true effects, β iq , within each campaign is given by N (β i , τ 2 2 ); and the distribution of realized experiment treatment effects, βiq , is N (β iq , σ 2 iq ). We again fit this via maximum likelihood for each outcome separately and then for Overall.…”
Section: Incorporating Heterogeneous Effects Across Experimentsmentioning
confidence: 99%
“…Looking across all studies, we can then see whether interventions had an impact on the binary outcome of interest. 2 This approach is similar in spirit to the approach taken by other papers that aggregate a set of experiments with distinct outcomes. 3 Overall, our combined findings suggest that these campaigns were effective at influencing peoples' attitudes and beliefs about the vaccine.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 This scalability includes not just reaching more people but also reaching individuals who may be hard or costly to reach via other means. This may be particularly important for some subpopulations where there is evidence of a disproportionate impact of the pandemic [2]. 5 A separate branch of literature has evaluated impacts of interventions on other COVID-related behaviors.…”
Section: Introductionmentioning
confidence: 99%